Effects of surface treatments on environmentally-assisted cracking susceptibility of Alloy 182 in BWR environment. (1st August 2021) - Que, Z.; Volpe, L.; Toivonen, A.; Burke, M.G.; Scenini, F.; Ehrnstén, U.
Highlights: Machining processes affect the near surface region microstructure of A182. Machining processes affect the EAC initiation threshold stress of A182 in BWR. The machining-induced deformation structure affect the EAC initiation and growth. The EAC initiation susceptibility at 1 × 10 −7 s −1 shows that SP > STI > RS > SAM. Abstract: The effects of four machining surface preparations on the environmentally-assisted cracking (EAC) initiation and early crack growth were evaluated for Alloy 182 flat tapered specimens exposed to a simulated boiling water reactor (BWR) environment under constant extension rate tensile test conditions. Results showed that the apparent EAC critical threshold stress for initiation was highly dependent on the surface treatment. Detailed microstructural characterization revealed the nature of the machining-induced deformation associated with the four surface treatments. Surface treatments affected the surface oxidation during exposure in the simulated BWR environment. The machining-induced deformation structure affected the EAC initiation susceptibility.